2006
DOI: 10.1136/thx.2005.052241
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial hyperresponsiveness and the development of asthma and COPD in asymptomatic individuals: SAPALDIA Cohort Study

Abstract: Background: Bronchial hyperresponsiveness (BHR) is a common feature of asthma. However, BHR is also present in asymptomatic individuals and its clinical and prognostic significance is unclear. We hypothesised that BHR might play a role in the development of chronic obstructive pulmonary disease (COPD) as well as asthma. Methods: In 1991 respiratory symptoms and BHR to methacholine were evaluated in 7126 of the 9651 participants in the SAPALDIA cohort study. Eleven years later 5825 of these participants were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
106
2
10

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(129 citation statements)
references
References 48 publications
6
106
2
10
Order By: Relevance
“…The causal relationship between an individual gene (molecule) and the phenotype (AHR) may be unclear because of its complex pathological processes in advanced patients with asthma, such as airway inflammation and structural remodeling. Besides the symptomatic patients, prospective studies revealed that some of the asymptomatic young adults also exhibit AHR (25) and it is thought to be a possible risk factor for future onset of asthma (26,27). In addition, associated factors such as atopy may partly contribute to the relationship (28).…”
Section: Discussionmentioning
confidence: 99%
“…The causal relationship between an individual gene (molecule) and the phenotype (AHR) may be unclear because of its complex pathological processes in advanced patients with asthma, such as airway inflammation and structural remodeling. Besides the symptomatic patients, prospective studies revealed that some of the asymptomatic young adults also exhibit AHR (25) and it is thought to be a possible risk factor for future onset of asthma (26,27). In addition, associated factors such as atopy may partly contribute to the relationship (28).…”
Section: Discussionmentioning
confidence: 99%
“…Отсюда следует, что, будучи предиктором тяжести течения ХОБЛ, ОФВ1 не является маркером активности заболевания, которую, вероятнее всего, следует отождествлять со скоростью снижения ОФВ1 [3,7]. Установлено, что факторами, влияющими на прогрессирование ХОБЛ, являются табакокурение [8], гиперреактив-ность бронхов (БГР) [9], частота обострений заболе-ваний [10], выраженность эмфиземы и бронходила-тационного ответа [3], а также фармакотерапия [11,12]. Следует отметить также, что, помимо ОФВ1, предикторами прогрессирования и летальности при ХОБЛ выступают и другие клинико-функциональ-ные признаки заболевания.…”
Section: оригинальные исследованияunclassified
“…Asymptomatic AHR is a risk factor for the development of asthma and COPD and is associated with new symptoms of wheeze, chronic cough, and annual loss of forced expiratory volume in 1 second (FEV 1 ). 16,17 Furthermore, AHR has been shown to be an important risk factor in patients with established asthma and COPD: more severe AHR is associated with more severe symptoms and a more rapid decline in FEV 1 .…”
Section: Airway Hyperresponsivenessmentioning
confidence: 99%